2004
DOI: 10.1021/jp049314p
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a Heterogeneous Source of OClO from the Reaction of ClO Radicals on Ice

Abstract: Experiments presented in this contribution demonstrate a heterogeneous source of several chlorine oxides, in particular OClO and ClClO 2 , from ClO radicals passed over water-ice surfaces at low pressures. ClO radicals were generated in a flow system and reaction products were monitored by UV-vis absorption spectroscopy and time-of-flight mass spectrometry using electron-impact and resonance-enhanced multiphoton ionization, respectively. In all experiments an efficient release of OClO into the gas phase was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 66 publications
1
25
3
Order By: Relevance
“…A role for water ice as a reaction surface for adsorbed species may be a possible path to perchlorate chemistry. ClO radicals are readily produced by atmospheric oxidation of chlorine volatiles, and ClO can interact on ice to produce OClO when the ice sublimates [ McKeachie et al , 2004]. Chlorine dioxide (the OClO molecule is not to be confused with Cl‐O‐O, which is the chlorine peroxy radical, unfortunately also sometimes called “chlorine dioxide”) is a possible source of perchlorate because it can react with O 3 or O to make chlorine trioxide [ Wayne et al , 1995]: …”
Section: Possible Origins Of Perchlorate On Marsmentioning
confidence: 99%
“…A role for water ice as a reaction surface for adsorbed species may be a possible path to perchlorate chemistry. ClO radicals are readily produced by atmospheric oxidation of chlorine volatiles, and ClO can interact on ice to produce OClO when the ice sublimates [ McKeachie et al , 2004]. Chlorine dioxide (the OClO molecule is not to be confused with Cl‐O‐O, which is the chlorine peroxy radical, unfortunately also sometimes called “chlorine dioxide”) is a possible source of perchlorate because it can react with O 3 or O to make chlorine trioxide [ Wayne et al , 1995]: …”
Section: Possible Origins Of Perchlorate On Marsmentioning
confidence: 99%
“…To check the effect of the mass filter at different m/z setting, we repeated the experiment in which we detected the daughter ions of ClOOCl. After the rescaling, the overall consistency among the scaled spectra and the molecular beam results at 266 and 308 nm is significantly improved, except that the spectrum by McKeachie et al 14 16 prepared a pure ClOOCl sample in a neon matrix, the light scattering from the solid matrix limited their sensitivity in the absorbance determination; as a result, the weak absorption of ClOOCl at Ͼ300 nm could not been determined precisely. After correction for the ion flight times, a daughter ion should exhibit the same arrival time as its parent ion.…”
Section: ͑3͒mentioning
confidence: 99%
“…In addition, new laboratory data of absorption cross section of ClOOCl have revealed that the photolysis rate of this crucial molecule should be much slower than it was previously assumed 11. As a consequence of these new data, there is a renewed open debate about the chemical processes responsible for the “ozone hole”12, 13 and several investigations have been conducted in the last years to complete the understanding of this chemistry 14–16…”
Section: Introductionmentioning
confidence: 99%